Penerapan ISO/IEC 27001:2022 dalam Tata Kelola Keamanan Sistem Informasi: Evaluasi Proses dan Kendala - Rudolf Sinaga; Frangky Taan (FKOM UNIKU, 2024)
Implementing ISO/IEC 27001:2022 in information security management is crucial and timely due to the increasing cyber threats, the necessity for regulatory compliance, and the significance of information security as a competitive edge. The latest revision of this standard demands proper adaptation and implementation to ensure effective information security management across various organizations. This study examines the key components of ISO/IEC 27001:2022, including organizational context, leadership, planning, support, operations, performance evaluation, and improvement. It delves into the application of ISO/IEC 27001:2022 in security system governance, emphasizing how this standard can enhance risk management and information security within an organization. A case study on a logistics company adopting this standard was conducted to identify best practices, implementation challenges, and its impact on security and regulatory compliance. The study's findings demonstrate that implementing ISO/IEC 27001:2022 effectively improves an organization's information security posture by integrating security policies, procedures, and controls into business processes. These findings offer recommendations as practical guidelines for organizations aiming to strengthen their information security management through the adoption of globally recognized international standards.